2014
DOI: 10.1007/s00244-014-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Pesticide Residues in Vegetables From Farms, Markets, and a Supermarket Around Kwan Phayao Lake of Northern Thailand

Abstract: This study investigated organophosphorus (OP) residues in vegetables from 27 farms, 106 markets, and 1 supermarket around Kwan Phayao Lake, Northern Thailand, between August and September 2013. Types of vegetables sampled were all vegetables cultivated or sold around the study site. The most common OP pesticides detected in farm samples were chlorpyrifos (50 %), malathion (31.8 %), monocrotophos (31.8 %), diazinon (13.6 %), omethoate (13.6 %), and dicrotophos (9.1 %). The most common OP pesticides detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 15 publications
7
70
2
1
Order By: Relevance
“…This implies that pesticides are used widely and extensively in the cultivation of Chinese kale in Thailand. This finding is consistent with those previously observed pesticide contamination in vegetables both in Thailand and other Asian countries (Chang et al, 2005;Sapbamrer and Hongsibsong, 2014;Swarnam and Velmurugan, 2013). A recent study conducted in northern part of Thailand (Sapbamrer and Hongsibsong, 2014) found that vegetables collected from markets containing organophosphorus pesticides greater than MRLs.…”
Section: Pesticide Detected In Chinese Kale Samples and Incidence Of supporting
confidence: 93%
See 1 more Smart Citation
“…This implies that pesticides are used widely and extensively in the cultivation of Chinese kale in Thailand. This finding is consistent with those previously observed pesticide contamination in vegetables both in Thailand and other Asian countries (Chang et al, 2005;Sapbamrer and Hongsibsong, 2014;Swarnam and Velmurugan, 2013). A recent study conducted in northern part of Thailand (Sapbamrer and Hongsibsong, 2014) found that vegetables collected from markets containing organophosphorus pesticides greater than MRLs.…”
Section: Pesticide Detected In Chinese Kale Samples and Incidence Of supporting
confidence: 93%
“…A survey study in India found residues of many organophosphorus pesticides (e.g., chlorpyrifos, dimethoate, monocrotophos and profenofos) in 54% of the vegetable samples (Swarnam and Velmurugan, 2013). Recent study from Thailand (Sapbamrer and Hongsibsong, 2014) reported an overall pesticide detection rate in many vegetables purchased from the markets, of 25% (N = 106). This rate is still much lower than the rate of pesticide detection in the Chinese kale that was observed in this study.…”
Section: Pesticide Detected In Chinese Kale Samples and Incidence Of mentioning
confidence: 96%
“…A C C E P T E D ACCEPTED MANUSCRIPT 2 2 nutrients, fiber and vitamins (Swarnam & Velmurugan, 2013) yet are the main exposure pathway 45 of OPs to human body (Sapbamrer & Hongsibsong, 2014; Teresa Munoz-Quezada, et al, 2012). 46 (Chen, et al, 2012) reported that application of pesticides at the recommended dose on vegetables 47 is unlikely to pose any public health issues as long as it is applied according to good state 48 agricultural practices.…”
Section: A N U S C R I P Tmentioning
confidence: 97%
“…High moisture content in fruit vegetables increased pesticides 180 degradation (Sapbamrer & Hongsibsong, 2014 The detected eleven OPs obtained for the arithmetic mean, maximum and minimum values (µg 203 kg -1 , fresh weight) were listed in Table 4. The mean concentrations of OPs in total samples were 204 the highest for dichlorvos (84.3 µg kg -1 ), followed by methamidophos (82.2 µg kg -1 ), diazinon 205 (50.4 µg kg -1 ), parathion (15.6 µg kg -1 ), omethoate (8.8 µg kg -1 ), phorate (7.8 µg kg -1 ), 206 parathion-methyl (7.0 µg kg -1 ), dimethoate (6.7 µg kg -1 ), and fenthion (6.5 µg kg -1 ), with 207 fenitrothion (4.1 µg kg -1 ) and malathion (1.7 µg kg -1 ) being the lowest.…”
Section: Hazard Index (Hi) 156mentioning
confidence: 99%
“…Tanaman yang mengandung residu pestisida melebihi batas maksimum residu (BMR) dikatakan kurang aman dikonsumsi (10). Residu pestisida pada sayuran dipengaruhi oleh dosis aplikasi, frekuensi penyemprotan, dan waktu aplikasi (12)(13). Oleh sebab itu pengawasan penggunaan pestisida harus dilakukan oleh instansi terkait untuk mencegah tingginya residu pestisida pada hasil pertanian.…”
Section: Pendahuluanunclassified